Korngruben fra Aabjerg: Opbevaring af afgrøder i senneolitikum og ældre bronzealder - Høyem Andreasen, Marianne; Helt Nielsen, Nina; Madsen, Malene (Kuml, 2025)
The grain pit at Aabjerg Crop storage in the Late Neolithic and Early Bronze Age Every now and again a pit containing a large amount of carbonized grain is found during an archaeological excavation. This phenomenon is mainly seen seen at Late Neolithic and Bronze Age sites. This article examines the interpretation of these pits. The storage of cereals is an important element in agricultural societies, where large amounts of grain, for food and seed corn, must be kept for a significant part of the year. In the Late Neolithic and Early Bronze Age there are rarely traces of utility buildings where the grain could have been stored. This means that there may have been other solutions apart from storage of grain in the main dwelling houses. Could storage of grain in a pit have been one of these solutions? The grain pit at Aabjerg is one of the features that may shed new light on this matter. In 2017, Museum Silkeborg excavated four houses and a large number of pits situated on a plateau in the Gudenå river valley near Resenbro, east of Silkeborg (figs. 1-2). The oldest house, which probably dates from the Single Grave culture (2350-2800 BC), was represented solely by a sunken floor. Three radiocarbon dates from a two-aisled longhouse fell in the range 2122-1885 BC, showing that the building was from the Late Neolithic, while the three most reliable radiocarbon dates for the two three-aisled houses fell within the range 1594-1289 BC, placing them in the Early Bronze Age. The most interesting feature on the site was, however, a pit (A223) situated quite close to the Late Neolithic house (A1001). The pit is probably contemporaneous with the house, as also indicated by radiocarbon dates from it (2131-1959 BC). When excavating the pit, it became clear that the lowermost 15 cm of the fill consisted of a compact, black layer of carbonized grain – some of which was still preserved as rachises, intact ears (figs. 3-6). The carbonized material from one half of the pit was sampled in two artificial layers in a grid of 3 x 5 squares, each measuring 30 x 30 cm. All in all, about 100 l of concentrated carbonized grain was collected. The archaeobotanical analysis of six subsamples of the carbonized material showed that it was completely dominated by grains of emmer/spelt and spikelet forks of emmer, whereas weed seeds and grains of naked barley, bread/durum wheat and einkorn were only found in small numbers, probably reflecting plants that were included unintentionally, for example when harvesting the fields (figs. 7-8; table 1). Sprouting was only observed on a single grain; brown bran was noted on a few grains. The interpretation of the pit contents is that they represent a single harvest of emmer. As the ratio of grains to glume bases is almost 1:1, it seems that the grain was in the form of spikelets when placed in the pit. This is also consistent with the observation of intact ears among the grain during excavation (fig. 9). This conclusion fits well with ethnoarchaeological studies undertaken by Gordon Hillman in Turkey. These showed that the composition, i.e. the relative amount of grain, other parts of the ear and weed seeds, depends on the stage in processing and cleaning the crop (fig. 10), and that emmer and other glume wheats were stored as spikelets/ears. Since the grain from Aabjerg appears to have been originally in the form of ears/spikelets, this suggests that the pit contents most likely represent the storage of emmer. Storage in underground pits/silos is known from both historical and modern times. Furthermore, successful experiments with storage of grain in pits have been carried out on Butser Ancient Farm in England. These showed that, in most cases, the grain was viable after storage, i.e. able to germinate, and that the water content, temperature and the development of fungi and bacteria could be kept under control. The most important conclusion was that the pits should be sealed at the top. In most cases this protected the grain very well, although the outermost few centimetres were always destroyed due to a greater water content, higher temperatures, more abundant fungi and a tendency to sprout here. During one very wet winter, however, a higher water content and consequent spontaneous heating destroyed the entire contents of the pit. Under ideal conditions, spontaneous heating should not take place in a grain storage pit. However, the experiments at Butser Ancient Farm, as well as experiments undertaken earlier, show that this can take place in the pits if the water and carbon dioxide contents rise. Spontaneous heating is also known from both early agricultural literature and modern agriculture, where, in worst cases, spontaneous combustion can occur if the crop is not stored under the correct conditions. It therefore seems likely that carbonization of the grains in the pit from Aabjerg could be due to this heating phenomenon. It may not have been the entire store of grain that became carbonized in the pit. Perhaps it was only the centre, which would explain the general lack of sprouting and the imperfect carbonization of the grains with the preserved brown bran. This possibility is supported by the fact that the spontaneous heating in the Butser Ancient Farm experiments was greatest near the centre of the pit, and that this phenomenon has also been noted in modern agriculture. The grain pit at Aabjerg provides a useful insight into how Late Neolithic people addressed the challenges related to the storage of grain. It is quite possible that not all the harvested crops were stored in this way. Perhaps it was only the surplus from very successful years that was stored in pits. This might provide an explanation for why the number of grain storage pits rises in the Late Neolithic. There seems to have been an increased focus on agriculture at this time as a greater variety of different crops was grown on each settlement. This may have resulted in a greater surplus which required storage. Pits containing large amounts of grain have been recorded at other Late Neolithic and Bronze Age settlements in Denmark. Only a few of these have been analysed, even though they hold a great potential for providing new insights into agriculture and society in the Late Neolithic. Future research must focus on the collective archaeological evidence and results of archaeobotanical and other scientific analyses from several sites. Only in this way will it be possible to identify the general strategy for storage of grain during the Late Neolithic. Moreover, such research would provide a valuable insight into agricultural practices, such as manuring strategies and agricultural processes. Grain pits, both those already excavated and those still to be found during future excavations, therefore deserve our full attention.